Pore structure and fractal characteristics of the marine shale of the longmaxi formation in the changning area, Southern Sichuan Basin, China - Li, Hu; Zhou, Jiling; Mou, Xingyu; Guo, Hongxi; Wang, Xiaoxing; An, Hongyi; Mo, Qianwen; Long, Hongyu; Dang, Chenxi; Wu, Jianfa; Zhao, Shengxian; Wang, Shilin; et al. (Frontiers in Earth Science, 2022)
The pore structure is an important factor affecting reservoir capacity and shale gas production. The shale reservoir of the Longmaxi Formation in the Changning area, Southern Sichuan Basin, is highly heterogeneous and has a complex pore structure. To quantitatively characterize the shale’s pore structure and influencing factors, based on whole rock X-ray diffraction, argon ion polishing electron microscopy observations, and low-temperature nitrogen adsorption-desorption experiments, the characteristics of the shale pore structure are studied by using the Frenkel-Halsey-Hill (FHH) model. The research reveals the following: 1) The pores of the Longmaxi Formation shale mainly include organic pores, intergranular pores, dissolution pores and microfractures. The pore size is mainly micro-mesoporous. Both ink bottle-type pores and semiclosed slit-type pores with good openness exist, but mainly ink bottle-type pores are observed. 2) The pore structure of the Longmaxi Formation shale has self-similarity, conforms to the fractal law, and shows double fractal characteristics. Taking the relative pressure of 0.45 (P/P0 = 0.45) as the boundary, the surface fractal dimension Dsf and the structural fractal dimension Dst are defined. Dsf is between 2.3215 and 2.6117, and the structural fractal dimension Dst is between 2.8424 and 2.9016. The pore structure of micropores and mesopores is more complex. 3) The mineral components and organic matter have obvious control over the fractal dimension of shale, and samples from different wells show certain differences. The fractal dimension has a good positive correlation with the quartz content but an obvious negative correlation with clay minerals. The higher the total organic carbon content is, the higher the degree of thermal evolution, the more complex the pore structure of shale, and the larger the fractal dimension. The results have guiding significance for the characterization of pore structure of tight rocks.